2000
DOI: 10.1037/0022-0663.92.4.745
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics, vocabulary, and reading development in Chinese American and European American children over the primary school years.

Abstract: Forty European American (EA; 20 girls, 20 boys) and 40 second-generation Chinese American (CA; 20 girls, 20 boys) preschool and kindergarten children (mean age at Time 1 = 5.7 years) and their mothers, fathers, and teachers participated in 3 data collections (1993,1995, and 1997) to investigate sociocultural and family factors that contribute to children's academic achievement. CA children outscored EA children in mathematics at all 3 times. Initially, EA children outscored CA children in receptive English vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 38 publications
6
111
0
2
Order By: Relevance
“…The lower ratings of athletic competence could reflect the fact that CA children spent considerably less time on team sports (e.g. Huntsinger, Jose, Larson, Krieg, & Shaligram, 2000;Schneider, Hieshima, Lee, & Plank, 1994). The lower self-ratings on social acceptance may be influenced by the fact that the children's immigrant parents expected their children to spend more time on academic pursuits and music practice, which left them less time for interaction with peers (e.g., Schneider et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The lower ratings of athletic competence could reflect the fact that CA children spent considerably less time on team sports (e.g. Huntsinger, Jose, Larson, Krieg, & Shaligram, 2000;Schneider, Hieshima, Lee, & Plank, 1994). The lower self-ratings on social acceptance may be influenced by the fact that the children's immigrant parents expected their children to spend more time on academic pursuits and music practice, which left them less time for interaction with peers (e.g., Schneider et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have concluded that exposure to numeracy concepts (including number sense concepts) at home is important (Blevins-Knabe and Musun-Miller 1996;Huntsinger et al 2000;LeFevre et al 2009bLeFevre et al , c, 2002Pan et al 2006). In home numeracy studies, parent questionnaire or interview data have been used to demonstrate retrospectively through self-report methods that involvement in mathematical-type activities is related to scores on mathematical achievement tests (Blevins-Knabe and MusunMiller 1996;Huntsinger et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…In home numeracy studies, parent questionnaire or interview data have been used to demonstrate retrospectively through self-report methods that involvement in mathematical-type activities is related to scores on mathematical achievement tests (Blevins-Knabe and MusunMiller 1996;Huntsinger et al 2000). Furthermore, studies have shown that differences exist for children as young as 3 to 4 years of age, living in varied environments, suggesting that the preschool environment is important for numeracy learning (Blevins-Knabe 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, early literacy skills can be encouraged through a variety of activities, such as shared book reading, telling stories, and exposure to the alphabet (Beaty and Pratt 2007; see also Richgels 2003), while early numeracy skills can be encouraged through activities such as counting, comparing sizes, and learning numbers (Silinskas et al 2010;Kuger and Kluczniok 2008). Engaging children in these activities at home and in preschools has proven to be fundamental to childhood development (LeFevre et al 2010;Howes et al 2008;Huntsinger et al 2000). The extensive research on early literacy has led to varying models and frameworks for this concept.…”
Section: Literacy and Numeracy Activities In Preschoolmentioning
confidence: 99%